EDUCATION IN BORDER REGIONS - Farid wadjdy (Faculty of Educational Sciences, Syarif Hidayatullah State Islamic University, 2017)
Abstract This paper aims to figure out the government policy in education management, community participation, and accessibility in border area. The qualitative framed theory with case study approach was used as the method of this study. The results showed that government was enacting special policies in national school operational assistance, providing block grant funds, special allowances for teachers and education personnel in border areas. Participation of the community was in the form of building dormitory in mutual assistance; customary heads took the legal role of school land and cultural preservation through extracurricular activities. Implementation of education in the form of nationalism enhancement assisted by the Indonesian National Army, facilities and school infrastructure were still under the national standards, teachers and employees were not disciplined, and supervision had not functioned optimally. When the teacher had given an assignment out of the region sometimes they had to leave their teaching job for up to two weeks late due to difficult. Abstrak Artikel ini bertujuan untuk meninjau kebijakan pemerintah dalam manajemen pendidikan, partisipasi masyarakat, dan aksesibilitas di daerah perbatasan. Teori yang dirumuskan secara kualitatif dengan pendekatan studi kasus digunakan sebagai metode penelitian ini. Hasil penelitian menunjukkan bahwa pemerintah memberlakukan kebijakan khusus dalam bantuan operasional sekolah nasional, menyediakan dana hibah blok, tunjangan khusus yang diperuntukan bagi guru dan tenaga kependidikan di daerah perbatasan. Partisipasi masyarakat adalah dalam bentuk membangun asrama dalam bantuan timbal balik; Kepala adat mengambil peran hukum pada ranah sekolah dan pelestarian budaya melalui kegiatan ekstrakurikuler. Pengimplementasian pendidikan dalam bentuk peningkatan nasionalisme dibantu oleh Tentara Nasional Indonesia, fasilitas dan infrastruktur sekolah masih di bawah standar nasional, guru dan karyawan yang tidak disiplin, dan pengawasan tidak berfungsi secara optimal. Ketika guru telah diberikan tugas di luar daerah, kadang-kadang mereka harus meninggalkan pekerjaan mengajar mereka hingga dua minggu lebih lama dari waktu yang ditugaskan karena akses yang tidak mudah dijangkau. How to Cite : Wadjdy, F. (2017). Education in Border Regions. TARBIYA: Journal of Education in Muslim Society, 4(2), 224-231. doi:10.15408/tjems.v4i2.6982. Permalink/DOI: http://dx.doi.org/10.15408/tjems.v4i2.6982